2009
DOI: 10.1159/000266478
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Receptor Blocker Reduces Proteinuria Independently of Blood Pressure in Children Already Treated with Angiotensin-Converting Enzyme Inhibitors

Abstract: Background/Aims: Dual blockade of the renin-angiotensin system with angiotensin-converting enzyme inhibitors (ACEI) and angiotensin receptor blockers (ARB) has higher antiproteinuric effects than single blockade in adults. In children, little is known on dual blockade of the renin-angiotensin system. The study investigates whether adding an ARB to proteinuric children already on ACEI reduces proteinuria. Methods: A total of 10 children (median age 13.3 years) with chronic kidney disease and persistent proteinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…A small randomized double blind cross-over trial in children with proteinuric renal disease demonstrated a similar reduction in proteinuria with ACE inhibitor compared with ARB, a finding that has been confirmed with a more recent larger trial [46,47]. Combined use of ACE inhibitors and ARBs has shown additional reduction in proteinuria with both agents in two small studies in children [48,49]. The KDIGO authors caution that risks of renin-angiotensin system blockers include hypotension in susceptible individuals, hyperkalemia, acute kidney injury during dehydrating illness, and teratogenicity if pregnancy occurs [16].…”
Section: First-line Antihypertensive Medicationmentioning
confidence: 75%
“…A small randomized double blind cross-over trial in children with proteinuric renal disease demonstrated a similar reduction in proteinuria with ACE inhibitor compared with ARB, a finding that has been confirmed with a more recent larger trial [46,47]. Combined use of ACE inhibitors and ARBs has shown additional reduction in proteinuria with both agents in two small studies in children [48,49]. The KDIGO authors caution that risks of renin-angiotensin system blockers include hypotension in susceptible individuals, hyperkalemia, acute kidney injury during dehydrating illness, and teratogenicity if pregnancy occurs [16].…”
Section: First-line Antihypertensive Medicationmentioning
confidence: 75%
“…The recommended doses should be similar to those administered to non-transplanted children (Table 4). Combination ACEI/ARB therapy was found to further reduce proteinuria by 30-40 % in non-transplanted children already on maximal doses of ACEIs [63]. This combination is also possible in transplanted patients [17], but caution must then be taken due to the increased risk of hyperkalemia or acute deterioration of the GFR, especially if the child is dehydrated.…”
Section: Causal Treatmentmentioning
confidence: 99%
“…332 In children who have received a kidney transplant, hypertension is a strong predictor of accelerated GFR decline 333 and graft loss. 334, 335 Preliminary data from the ongoing observational Chronic Kidney Disease in Children (CKiD) study show that, among 425 children with repeated measures of GFR, having systolic BP above the 90 th percentile for age, sex, and height is associated with faster progression of CKD as compared with lower BP. 336 In this cohort, the annualized percent change in GFR among those with systolic BP above the 90 th percentile was −7.5 ml/min/1.73 m 2 (95% CI −16.6–0.1), compared to −3.8 (95% CI −11.8–3.8) in those with systolic BP between the 50 th and 90 th percentiles and −2.5 (95% CI −8.9–3.9) in those with systolic BP below the 50 th percentile.…”
Section: Rationalementioning
confidence: 99%
“…Small randomized trials of combinations of ACE-Is and ARBs in children with CKD demonstrate significant reductions in urine protein levels as compared to the use of only one of the drug classes. 335, 352 However, further study of long-term outcomes and safety data are necessary.…”
Section: Rationalementioning
confidence: 99%